Localization and size quantification of surface crack of concrete based on Rayleigh wave attenuation model. (19th April 2021) - Yu, Haifan; Lu, Linjun; Qiao, Pizhong
Highlights: A theoretical method for localization and size quantification of surface crack of concrete by Rayleigh wave is proposed. Crack tip and midrange are quantitatively distinguished by the wave attenuation model. A modified ellipse localization algorithm is employed to determine the crack endpoints, crack midrange and orientations. Abstract: Damage detection is one of the most important major branches of non-destructive evaluation. In this study, a damage detection method for localization and size quantification of surface crack of concrete based on a Rayleigh wave attenuation model is proposed. A new physical Rayleigh wave attenuation model considering both the material and geometrical attenuation coefficients is developed, in which systematic search method and numerical integration are employed to solve the implicit integration function. Based on the proposed attenuation model, the difference of wave attenuation ratio at different reflection positions (i.e., crack tip and midrange) is investigated and further validated by comprehensive numerical models. It is proven that the proposed attenuation model and criterion can be successfully employed to quantitatively recognize the signals reflected from different positions of crack. With the accurate recognition of crack tip and midrange, a modified ellipse localization algorithm is proposed to determine the linear and broken-line crack endpoints and orientation in four generalized cases. The results show that the detected location and length of crack agree well with that of originally precast crack. The proposed method for crack localization and size quantification of surface crack based on the wave attenuation model shows great potential for damage severity detection of concrete structures.